PENDIDIKAN ISLAM DI SPANYOL - Mulyadi Hermanto Nasution (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
This paper provides a brief overview of the development of Islamic  education.  One  thing  that  is  interesting  that  the transition   of   civilization   of   the   Islamic   world   to   the European   part   can   occur   through   the   development   of Islamic  education  in  stages,  making  European  civilization can  rise  up  to  this  day.  The  progress  of  the  European world  to  date  has  a  very  dynamic  history.  This  is  seen  by the many scholars who can trace the progress through the process of in-depth review. Therefore, it can be stated that the  existence  of  Islamic  educational  process  in  Spain  can provide   influenced   by   the   opening   of   the   realm   of philosophy as one of the main keys in the birth of various disciplines in Islam.